Fungal community in antarctic soil along the retreating collins glacier (Fildes peninsula, King George Island) - dos Santos, Juliana Aparecida [UNESP]; Meyer, Edenilson; Sette, Lara Durães [UNESP] (MDPI, 2020)
Glacial retreat is one of the most conspicuous signs of warming in Antarctic regions. Glacier soils harbor an active microbial community of decomposers, and under the continuous retraction of glaciers, the soil starts to present a gradient of physical, chemical, and biological factors reflecting regional changes over time. Little is known about the biological nature of fungi in Antarctic glacier soils. In this sense, this work aimed at studying the behavior of fungal community structure from samples of glacier soil collected after glacial retreat (Collins Glacier). A total of 309 fungi distributed in 19 genera were obtained from eleven soil samples. Representatives of the genera Pseudogymnoascus (Ascomycota) and Mortierella (Mortierellomycota) were the most abundant isolates in all samples. The data revealed the presence of filamentous fungi belonging to the phylum Basidiomycota, rarely found in Antarctica. Analysis of the generalized linear models revealed that the distance from the glacier as well as phosphorus and clay were able to modify the distribution of fungal species. Environmental variations proved to have influenced the genera Pseudogymnoascus and Pseudeutorium.
Keywords: Antarctic microbiology; Extremophiles; Fungal diversity; Glacial soil; Glacier retraction